Association of potentially functional variants in the XPG gene with neuroblastoma risk in a Chinese population - He, Jing; Wang, Fenghua; Zhu, Jinhong; Zhang, Ruizhong; Yang, Tianyou; Zou, Yan; Xia, Huimin (Journal of cellular and molecular medicine, 2016)
XPG gene plays a critical role in the nucleotide excision repair pathway. However, the association between XPG gene polymorphisms and neuroblastoma risk has not been investigated. In this study with 256 neuroblastoma cases and 531 cancer‐free controls, we investigated the effects of five potentially functional polymorphisms (rs2094258 C>T, rs751402 C>T, rs2296147 T>C, rs1047768 T>C and rs873601G>A) on neuroblastoma risk. We calculated odds ratio (OR) and 95% confidence interval (CI) to evaluate the association between the five selected polymorphisms and neuroblastoma risk. False‐positive report probability (FPRP) was utilized to determine whether significant findings were noteworthy or because of a chance. We also performed genotype–phenotype association analysis to explore the biological plausibility of our findings. We found that the rs2094258 T allele was significantly associated with decreased neuroblastoma risk (CT versus CC: adjusted OR = 0.65, 95% CI = 0.47–0.90, P = 0.010; and CT/TT versus CC: adjusted OR = 0.71, 95% CI = 0.53–0.97, P = 0.030) after adjusting for age and gender. The association was more prominent for subjects with retroperitoneal tumour or early‐stage tumour. We also found that carriers of the 2–3 risk genotypes had a significantly increased neuroblastoma risk when compared to carriers of the 0–1 risk genotypes. The association with risk genotypes was more predominant in older children, females and subjects with retroperitoneal tumour or early stage. Our results were further supported by FPRP analysis and genotype–phenotype association analysis. In conclusion, our study verified that the XPG gene rs2094258 C>T polymorphism may contribute to neuroblastoma susceptibility. Our findings require further validation by studies with larger sample size and concerning different ethnicities.